2011
DOI: 10.1111/j.1467-8748.2011.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

698. Fritillaria Usuriensis

Abstract: Fritillaria usuriensis Maxim. is illustrated; its cultivation in China for Chinese traditional medicine, and at Kew are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In April 2012, while conducting a fi eld trip in the Hawraman, western Iran, unusual specimens of Fritillaria were collected by Mahfouz Advay. Th e specimens were checked in the relevant literature; Grossheim (1935), Rix (1977Rix ( , 1984Rix ( , 1988, Townsend and Guest (1985), Feinbrun-Dothan (1986), Rechinger (1990), Khaniki (1997aKhaniki ( , 1997b, Khaniki and Persson (1997), Xinqi and Mordak 2000and Tek ş en and Ayta ç (2011. Further studies showed that they were not referable to any known taxon of the genus, and therefore F. avromanica is described here as a new species.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In April 2012, while conducting a fi eld trip in the Hawraman, western Iran, unusual specimens of Fritillaria were collected by Mahfouz Advay. Th e specimens were checked in the relevant literature; Grossheim (1935), Rix (1977Rix ( , 1984Rix ( , 1988, Townsend and Guest (1985), Feinbrun-Dothan (1986), Rechinger (1990), Khaniki (1997aKhaniki ( , 1997b, Khaniki and Persson (1997), Xinqi and Mordak 2000and Tek ş en and Ayta ç (2011. Further studies showed that they were not referable to any known taxon of the genus, and therefore F. avromanica is described here as a new species.…”
Section: Methodsmentioning
confidence: 99%
“…Th e specimens belonging to F. avromanica have yellow anthers during early anthesis and then blackish anthers, and much broader leaves. Also F. assyriaca is widespread and very variable, especially in leaf width according to Rix (1977). But it has always yellow anthers and up to 12 mm wide lowest leaves.…”
Section: Similar Speciesmentioning
confidence: 99%
See 2 more Smart Citations